GANGGUAN PENGHIDU PADA PEKERJA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DI YOGYAKARTA - , Azhar Nur Fathoni ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The nose is the olfactory organ in human, plays an important role to protect people from environmental hazards. One of the causes of olfactory malfunction is exposure to gasoline fumes. Gasoline containing volatile substances BTEX (benzene , toluene , ethylbenzene and xylene) which can cause damage to the olfactory epithelium when exposed to chronic. Objective: To determine differences of olfactory function impairment in workers General Fuel Filling Station (gas stations) than non-working gas station in Yogyakarta Methods: The design was a cross sectional study. The study subjects were 74 people, who work in gas station in Yogyakarta as a group of exposed subjects and who do not work in gas station as a group of non exposed subjects, which meets the criteria for inclusion and exclusion. Smell disorder diagnosis is made by using the Sniffin's Olfactory Screening Test 12. Statistical analysis used chi square is , Prevalence Ratios , logistic regression Results: Based on the results that obtained in the examination of the function of the olfactory of gas station worker groups of 23 people ( 31.1 ) and in the nonworking gas station of 7 people ( 9.46 ) with p=0.0001 with value Prevalence Odds Ratio of 7.041 ( CI 95 % = 2.44 to 20.27 ) . With exposure to gasoline vapor that was 7.041 times for the risk of disruption to the function of olfactory. Conclusions: There are significant differences in function disorders caused by exposure to gasoline fumes olfactory the gas station workers compared to workers instead of filling stations in the city of Yogyakarta Keywords : olfactory function, gas station workers, gasoline vapors, Sniffin 's test.